One ion to catch them all: Targeted high-precision Boltzmann thermometry over a wide temperature range with Gd3+ - Dechao Yu (Nature Publishing Group, 2021)
Abstract Ratiometric luminescence thermometry with trivalent lanthanide ions and their 4f n energy levels is an emerging technique for non-invasive remote temperature sensing with high spatial and temporal resolution. Conventional ratiometric luminescence thermometry often relies on thermal coupling between two closely lying energy levels governed by Boltzmann’s law. Despite its simplicity, Boltzmann thermometry with two excited levels allows precise temperature sensing, but only within a limited temperature range. While low temperatures slow down the nonradiative transitions required to generate a measurable population in the higher excitation level, temperatures that are too high favour equalized populations of the two excited levels, at the expense of low relative thermal sensitivity. In this work, we extend the concept of Boltzmann thermometry to more than two excited levels and provide quantitative guidelines that link the choice of energy gaps between multiple excited states to the performance in different temperature windows. By this approach, it is possible to retain the high relative sensitivity and precision of the temperature measurement over a wide temperature range within the same system. We demonstrate this concept using YAl3(BO3)4 (YAB):Pr3+, Gd3+ with an excited 6P J crystal field and spin-orbit split levels of Gd3+ in the UV range to avoid a thermal black body background even at the highest temperatures. This phosphor is easily excitable with inexpensive and powerful blue LEDs at 450 nm. Zero-background luminescence thermometry is realized by using blue-to-UV energy transfer upconversion with the Pr3+−Gd3+ couple upon excitation in the visible range. This method allows us to cover a temperature window between 30 and 800 K.